Effect of microabsorption on the determination of amorphous content via powder X-ray diffraction. Issue 1 (22nd March 2018) - Scarlett, Nicola V. Y.; Madsen, Ian C.
Abstract : Powder X-ray diffraction has become a routine procedure for the quantification of phases in mixtures. The most common method for this measurement is the Rietveld method, which generally returns the relative weight percentages of the crystalline components within the mixture. However, in many instances, it is also desirable to obtain an estimate of the amorphous content of a sample. There are several methods that may be used for this measurement and their accuracy has been assessed previously with a number of ideal, synthetic mixtures. Many samples, especially in the mineralogy sphere, are far from ideal and contain multiple phases of varying absorption contrast. This creates a microabsorption problem which affects the accuracy of the determination of both the crystalline and amorphous components. This paper assesses commonly used methods of amorphous determination with a series of synthetic samples designed to create a considerable microabsorption problem.